Toward a Global Bioethics: Principlism and the Problem of Political Legitimacy. - Annoni, Marco (Bioethics, 2026)
Tom Beauchamp and James Childress's Principles of Biomedical Ethics introduced principlism—or the "four principles approach"—which has since become one of the most influential frameworks in contemporary bioethics. However, its potential to serve as a foundation for shared transcultural bioethical norms has elicited both substantial support and considerable critique. In this article, I analyze two notable attempts that utilize, or appear to be modeled after, principlism as a basis for global bioethics: Beauchamp and Childress's original formulation and the recently revised International Code of Medical Ethics by the World Medical Association. I argue that each model fails, but for different reasons. Beauchamp and Childress's account is rooted in particular moralities, making it suitable for guiding action in specific clinical contexts but ill‐equipped to handle global ethical pluralism. Conversely, the WMA's approach is deficient due to its undefined moral foundation and lack of political legitimacy. To address these shortcomings, I outline a third approach designed to make explicit the connection between principlism, global bioethics, and the problem of political legitimacy.